The Military, the media and the invasion of Grenada - Block, Marcia (Contemporary crises, 1989)
The article begins by discussing trends in official U.S. information policies before the invasion of Grenada (1983), describing the tendency towards secrecy and limited disclosure. The immediate political background to the invasion is outlined, including an examination of attempts to produce a plausible justification for military intervention. The "management" of the media both immediately before and after the invasion is detailed and the article concludes by assessing the lessons and aftermaths of the "information war" fought during the Grenada episode.